Effect of UV-B Irradiation on Water-Suspended Metarhizium anisopliae s.l. (Hypocreales: Clavicipitaceae) Conidia and Their Larvicidal Activity in Aedes aegypti (Diptera: Culicidae) - Falvo, Marianel Lucía (2018)
Ultraviolet (UV) radiation is a key limiting factor for biological pest control with entomopathogenic fungi. While littleis known about the impact of UV on Metarhizium anisopliae Metchnikoff (Sorokin) (Hypocreales: Clavicipitaceae)conidia in aquatic mosquito-breeding sites, this study determined the effect of UV-B on the viability and virulenceof M. anisopliae sensu lato (s.l.) strain IP 46 in the laboratory against Aedes aegypti (L.) (Diptera: Culicidae) larvae.Conidia were treated in cups under defined water depths (0, 1, 2, and 3 cm) to six different UV-B doses (0, 0.657,1.971, 3.942, 7.884, 11.826, or 15.768 kJ m−2) at 27 ± 2°C. The ability of treated conidia to germinate up to 24 hpostexposure on PDAY + benomyl + chloramphenicol medium at 25 ± 1°C was adversely affected by higher dosesof UV-B radiation regardless of the water depth. Germination, however, did not fall below 70% regardless of thetest conditions. In fact, conidial virulence against second-instar larvae was not affected by either the water depth(F3,84 = 0.3, P = 0.85) or any tested levels of UV-B radiation (F6,21 ≤ 1.2, P ≥ 0.39) including those distinctly higher thanmight be expected for tropical sites. These findings strengthen previous observations that IP 46 has significantpotential for use against A. aegypti larvae, even when exposed to elevated UV-B irradiance levels in the smallbreeding sites that are common for this important vector.